Idiopathic Atrophoderma of Pasini and Pierini: Case report and literature review. Issue 2 (18th December 2018) - Muntyanu, Anastasiya; Redpath, Margaret; Roshdy, Osama; Jfri, Abdulhadi
Key Clinical Message: Idiopathic Atrophoderma of Pasini and Pierini should be considered on the differential in a patient presenting with an asymptomatic atrophic plaque on the skin. Differentiation from Linear Atrophoderma of Moulin and morphea remains a challenge; however, features of the presentation and tissue biopsy can help establish the diagnosis. Abstract : Idiopathic Atrophoderma of Pasini and Pierini should be considered on the differential in a patient presenting with an asymptomatic atrophic plaque on the skin. Differentiation from Linear Atrophoderma of Moulin and morphea remains a challenge; however, features of the presentation and tissue biopsy can help establish the diagnosis.